Effects of water flow and ocean acidification on oxygen and pH gradients in coral boundary layer - Martins, Catarina P. P.; Ziegler, Maren; Schubert, Patrick; Wilke, Thomas; Wall, Marlene; Justus Liebig University Giessen (My University, 2024)
Reef-building corals live in highly hydrodynamic environments, where water flow largely controls the complex chemical microenvironments surrounding them—the concentration boundary layer (CBL). The CBL may be key to alleviate ocean acidification (OA) effects on coral colonies by partially isolating them. However, OA effects on coral CBL remain poorly understood, particularly under different flow velocities. Here, we investigated these effects on the reef-building corals Acropora cytherea, Pocillopora verrucosa, and Porites cylindrica. We preconditioned corals to a control (pH 8.0) and OA (pH 7.8) treatment for four months and tested how low flow (2 cm s−1) and moderate flow (6 cm s−1) affected O2 and H+ CBL traits (thickness, surface concentrations, and flux) inside a unidirectional-flow chamber. We found that CBL traits differed between species and flow velocities. Under OA, traits remained generally stable across flows, except surface pH. In all species, the H+ CBL was thin and led to lower surface pH. Still, low flow thickened H+ CBLs and increased light elevation of surface pH. In general, our findings reveal a weak to null OA modulation of the CBL. Moreover, the OA-buffering capacity by the H+ CBL may be limited in coral species, though low flow could enhance CBL sheltering.
Keywords: ddc:570